Mineral Facilitated Horizontal Gene Transfer: A New Principle for Evolution of Life? - Sand, Karina Krarup; Jelavić, Stanislav (Frontiers in Microbiology, 2018)
A number of studies have highlighted that adsorption to minerals increases DNA longevity in the environment. Such DNA-mineral associations can essentially serve as pools of genes that can be stored across time. Importantly, this DNA is available for incorporation into alien organisms through the process of horizontal gene transfer. Here we argue that minerals hold an unrecognized potential for successfully transferring genetic material across environments and timescales to distant organisms and hypothesize that this process has significantly influenced the evolution of life. Our hypothesis is illustrated in the context of the evolution of early microbial life and the oxygenation of the Earth’s atmosphere and offers an explanation for observed outbursts of evolutionary events caused by horizontal gene transfer.